(3GdeMGSHI GdGOGQjIs - (3eDjO(B, (3eMeO GdaVds; (3YHO GdfGUQ GHQGgje fhe(B, s ((3YeGf(B:s (3GdeSjQI(B,s, 2007)
(3GdGWGQ GdacQj h GdeaGgjej ddeMGSHI GdGOGQjI , CfhGY GdJcGdja ef efXhQ GdeMGSHI GdGOGQjI , fXe JMejd GdJcGdja h JNWjW GdeHjYGJ , JMdjd YdGbI GdcdaI (B- (3GdMLe (B- (3GdQHM eY JfGhd GdehGRfGJ h GdehGRfI GdQCSeGdjI , GdJcGdja GdedGFeI dEJNGP GdbQGQGJ bUjQI GdCLd h CNjQG GddGeQcRjI h eMGSHI GdeSDhdjI h CSYGQ GdJMhjd eY hLhO CSFdI h JeGQjf ddeQGLYI aj fgGjI cd aUd(B.s
Keywords: (3GdGOGQIs; (3GdeMGSHIs; (3GdeMGSHI GdEOGQjIs